Językowy kształt tekstów agitacyjnych wprowadzających Chorwację do Unii Europejskiej - Błachowicz, Ewa; Błachowicz-Wolny, Anna (Słowo. Studia językoznawcze, 2013)
The authors present the image of agitation campaign introducing Croatia into European Union. It is composed of two parts. The former is devoted to information embedded in culture-related and political reality while the latter is an attempt at presenting diverse forms of canvassing. The analysis addresses leaflets, brochures, TV commercials, graffiti as well as the input by Internet users. The coherence of such ‘spatial’ diversity springs from illocution, which assumes the identity of the aim, namely: to encourage electors to vote or to discourage them from voting. The analysis shows the mechanisms of persuasion and manipulation as well as the linguistic means employed by authors of such texts.